2018
DOI: 10.1177/0741932518778029
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Interagency Collaboration: Relationships Between Secondary Transition Roles, Communication, and Collaboration

Abstract: A web-based survey was disseminated to examine the relationship between high school special education teachers and direct-service transition professionals’ understanding of stakeholders’ roles in transition, frequency of communication with transition stakeholders, and level of collaboration among stakeholders. Path analyses were also conducted to determine the predictive relationship between understanding of roles, frequency of communication, and level of collaboration between high school special education and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 27 publications
0
14
0
1
Order By: Relevance
“…To ensure a successful transition from school to the adult services delivery system, research indicates that schools and outside agencies must share responsibility in promoting interagency collaboration (Plotner et al, 2020;Shogren & Wittenburg, 2020). This collaboration has been shown to be a predictor of improved post-school outcomes; although evidence-based strategies to facilitate interagency collaboration have yet to be identified .…”
Section: Interagency Collaborationmentioning
confidence: 99%
See 1 more Smart Citation
“…To ensure a successful transition from school to the adult services delivery system, research indicates that schools and outside agencies must share responsibility in promoting interagency collaboration (Plotner et al, 2020;Shogren & Wittenburg, 2020). This collaboration has been shown to be a predictor of improved post-school outcomes; although evidence-based strategies to facilitate interagency collaboration have yet to be identified .…”
Section: Interagency Collaborationmentioning
confidence: 99%
“…The transition process can be especially daunting for students with autism spectrum disorder (ASD) due to difficulties in social interaction, regulating sensory experiences, and engaging in activities outside of a narrow range of interests (American Psychiatric Association, 2013;Hendricks, 2010;Hurlbutt & Chalmers, 2004;Silverman et al, 2014;Ward & Esposito, 2019). As a result, special education teachers often find it challenging to identify effective combinations of practices and supports to best serve the needs of these students (Mazzotti et al, 2016;Morningstar et al, 2010;Plotner et al, 2020;Test & Fowler, 2018;Trainor et al, 2020).…”
mentioning
confidence: 99%
“…Successful outcomes in competitive integrated employment for transition-aged adults with intellectual and developmental disabilities continue to be low throughout the United States, despite promising practices and policies, such as supported and customized employment, the Rehabilitation Act, the Workforce Innovations and Opportunity Act, Employment First, and most recently, the Home and Community-Based The first guiding principle of the USWI model is establishing meaningful, community-based secondary employment experiences. Researchers have consistently found that having one or more paid jobs during secondary education is one of the strongest predictors of post-secondary employment of young adults with disabilities (Carter et al, 2012;Mazzotti et al, 2014Mazzotti et al, , 2020Test et al, 2009). Although Utah schools often provide work-based learning (WBL) experiences during secondary education to their students with disabilities, the WBL experiences tend to be unpaid and are often with the same employers year after year.…”
Section: Introductionmentioning
confidence: 99%
“…The second guiding principle incorporated into our model, interagency collaboration of transition stakeholders, is another predictor of post-school success (Haber et al, 2016;Mazzotti et al, 2020;Test et al, 2009). We sustain interagency collabora- and (f) the philosophy that regardless of disability, everyone can be competitively employed.…”
Section: Introductionmentioning
confidence: 99%
“…El trabajo colaborativo es una celebración de la diversidad, un pequeño grupo de estudiantes podría ser cultural y socialmente muy diverso y, por lo tanto, los proyectos de aprendizaje colaborativo podrían abrir el mundo a los estudiantes a medida que comienzan a obtener una nueva perspectiva de la vida de sus compañeros. Los estudiantes también pueden reflexionar sobre sus vidas y valores frente a los de sus compañeros y aprenden a reconocer las diferencias sin ser críticos (Plotner, 2018). El trabajo colaborativo es una necesidad en la educación secundaria porque permite el desarrollo interpersonal: en una empresa de grupo, es fundamental que los estudiantes aprendan a trabajar con todo tipo de personas y a relacionarse con sus compañeros para que el proyecto en cuestión se beneficie de su interacción estructurada (Thibaut et al, 2018).…”
unclassified